Optimasi PC Tua Menggunakan Aplikasi Citrix Metaframe 1.8 Pada Sekolah Menengah Kejuruan Kanisius Bharata Karanganyar - Putro, Fx Sulistyo; Purnama, Bambang Eka (Seruni - Seminar Riset Unggulan Nasional Inoformatika dan Komputer, 2013)
Abstract : The development of information technology so rapidly, particularly in the development of computer software that the hardware needed to support the operation of the software. This result in the use of some software is often a problem for many institutions included educational institutions, due to the hardware required to use certain software that has minimal requirements specification software. The development of computer network technology (network) is also made in some quarters to continue to follow its development, especially education which used to seek the solution of a problem by seeking a breakthrough to optimize the appropriate use of computer technology. Kanisius Bharata Karanganyar Vocational School (SMK) by competency skills Computer Engineering and Networks still have the old generation personal computer (hereinafter called the old PC) are numerous and are not used anymore because there were no longer compatible with the software needed today. With PC clonning,the old or older computer generation PC-based processor 486 and Pentium I /100 can be optimized to Client PCs that have the performance equal to the server, Intel dual core uses Terminal Service facilities and software applications Citrix Metaframe 1.8 on Windows 2000 Server the local area network (LAN). PC clonning is one solution that can provide convenience especially efficient in the use of software and hardware, as software only applications installed on a server and then using Citrix Metaframe 1.8 applications all available resources on the server can be exploited by the Client PC. One of the problems facing by school where the author works, the authors tries to apply PC technology clonning and pour in writing under the title